2001
DOI: 10.1079/phn2001228
|View full text |Cite
|
Sign up to set email alerts
|

Dietary guidelines for the Spanish population

Abstract: Iodine deficiency disorders (IDD) are related to the degree of iodine deficiency. In european countries, characterized by mild to moderate iodine deficiency, neurological deficits or minor neuropsychological impairments have been described. Urinary iodine excretion (UIE) ranged from 30 to 170 mcg/L, 141 millions of people were at risk of IDD, 97 millions were affected by goiter and 0.9 millions had an impaired mental development. Iodine prophylaxis is devoid of adverse reactions with the exception of sporadic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 15 publications
1
40
0
3
Order By: Relevance
“…Such findings are in agreement with other studies conducted in the neighbouring Spain (Serra-Majem et al, 1993;Rodríguez-Artalejo et al, 1996), France (increase from 44 to 85 kg/year/person in 1950 and 1996, respectively) (Haut Comité de la Santé Publique, 2000) and Italy (increase from 50 to 100 g/day in 1960 and 1996, respectively) (de Lorenzo et al, 2001) but contrary to those found in Germany (decrease between 1.8 and 2.6 g/day per year) (Jungjohann et al, 2005) or USA (decrease from 32 to 20% of total fat in 1965 and 1995, respectively or from 8.9 to 3.1% of total energy in 1977 and 1995, respectively (Nielsen et al, 2002)). Overall, these data indicate that, like other southern European countries, the dietary pattern of the Portuguese population is shifting from a Mediterranean to a more Westernized type (Aranceta, 2001). Interestingly, the strongest increase in reported meat consumption was noted in the lower educated group, suggesting that this Trends of food intake in Portugal, 1987-1999 P Marques-Vidal et al 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 increase might partly be owing to better economical access to meat products (Haut Comité de la Santé Publique, 2000) or lack of education on health issues.…”
Section: Discussionmentioning
confidence: 59%
“…Such findings are in agreement with other studies conducted in the neighbouring Spain (Serra-Majem et al, 1993;Rodríguez-Artalejo et al, 1996), France (increase from 44 to 85 kg/year/person in 1950 and 1996, respectively) (Haut Comité de la Santé Publique, 2000) and Italy (increase from 50 to 100 g/day in 1960 and 1996, respectively) (de Lorenzo et al, 2001) but contrary to those found in Germany (decrease between 1.8 and 2.6 g/day per year) (Jungjohann et al, 2005) or USA (decrease from 32 to 20% of total fat in 1965 and 1995, respectively or from 8.9 to 3.1% of total energy in 1977 and 1995, respectively (Nielsen et al, 2002)). Overall, these data indicate that, like other southern European countries, the dietary pattern of the Portuguese population is shifting from a Mediterranean to a more Westernized type (Aranceta, 2001). Interestingly, the strongest increase in reported meat consumption was noted in the lower educated group, suggesting that this Trends of food intake in Portugal, 1987-1999 P Marques-Vidal et al 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 1987 1995-1996 1998-1999 increase might partly be owing to better economical access to meat products (Haut Comité de la Santé Publique, 2000) or lack of education on health issues.…”
Section: Discussionmentioning
confidence: 59%
“…Our study demonstrates that adolescents who are low consumers of total fat and SFA (consumption below the lower quartile) and high consumers of fruits and vegetables and dietary fiber (consumption above the upper quartile) showed better compliance with the 2010 nutritional objectives for the Spanish population than did high consumers of total fat and SFA and low consumers of fruits and vegetables and fiber. Overall, low consumers of fat and saturated fat and high consumers of fiber, fruit, and vegetables showed a food consumption pattern similar to that recommended in current food group pyramids [36,37] and in line with the traditional Mediterranean dietary pattern [38] and the traditional Balearic Islands diet present at the beginning of the 20th century [39]. The food patterns of the healthier adolescent consumers is quite similar to that observed in the Balearic Islands’ adult population, but adolescents need to improve their dietary pattern by decreasing meat consumption and increasing their consumption of pulses and fruits and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…FBDG were developed (2) and used internationally to express the principles of a balanced diet in terms of foods (3)(4)(5)(6)(7)(8)(9)(10) and to reduce the prevalence of obesity (11) and diet-related diseases. These guidelines are a more practical tool compared with the nutrient reference values, set at (inter-) national level (12,13) .…”
Section: Food Consumption Survey 24 H Recall Food-based Dietary Guidementioning
confidence: 99%